STUDY OF THE MATRIX STRUCTURE INFLUENCE ON THE RHEOLOGICAL CHARACTERISTICS OF NIMESULIDE ORAL GEL EXPERIMENTAL SAMPLES - M. N. Anurova; E. O. Bakhrushina; S. P. Krechetov (Разработка и регистрация лекарственных средств)
The article presents the results of the studying rheological characteristics of nimesulide oral gel experimental samples on the basis of the combined matrix. We have investigated influence of rheological properties of the nimesulide release from oral gels. We have established a gel with optimal rheological and biopharmaceutical characteristics.